[PP.33.05] BODY FAT COMPOSITION AFFECTS LEFT VENTRICULAR MASS IN HYPERTENSIVE WOMEN: A BIOIMPEDANCE STUDY. (September 2016) - Catena, C.; Colussi, G.L.; Novello, M.; Pezzutto, F.; Palomba, A.; Sechi, L.A.
Abstract : Objective: In addition to the hemodynamic load, other clinical and biochemical factors could contribute to the development of left ventricular (LV) hypertrophy in hypertensive patients. It is not clear, however, whether body composition in terms of fat and muscle mass is related to the LV mass and whether this relationship differs between genders. The aim of the study was to investigate the possible association between components of the body mass, as estimated by a bioimpedance analysis (BIA), and LV morphology and function in hypertension. Design and method: In 146 patients with essential hypertension (age 48 ± 13; 81 males; 49 never treated and 97 studied after drug wash-out of at least 2 weeks) we measured anthropometric and clinical variables, plasma insulin and fibrinogen levels, total body fat and free fat mass and body muscle mass by BIA, and performed conventional echocardiography Results: Men had higher systolic blood pressure and body free fat and muscle mass and lower total body fat mass than women. LV hypertrophy was detected according to consensus criteria in 42 (28%) patients who were older, had higher body mass index, blood pressure, total body fat mass and fibrinogen levels than patients without LV hypertrophy. In men, LV mass index was significantly and directly related to age, body mass index, blood pressure, and fibrinogen levels, whereas no relationship were observed with body fat composition. In women, LV mass index was directly related to body mass index, blood pressure, duration of hypertension, total body fat mass, and plasma insulin and fibrinogen levels. At multivariate regression analysis, LV mass index was related independently with age and blood pressure in men and with blood pressure, duration of hypertension, and fibrinogen levels in women Conclusions: LV mass index is related to body fat mass only in women, a relationship that is not independent and that appears to be mediated by higher plasma levels of insulin and fibrinogen.